Effect of deastringency treatment on carotenoid compounds of persimmon fruit - Novillo, Pedro; Besada, Cristina; Bermejo, Almudena; Navarro, Pilar; Salvador, Alejandra (ISHS, 2021)
Nowadays, consumers demand fresh fruits high in bioactive compounds because of their growing concern for health. Carotenoids are important bioactive compounds present in persimmon fruit and the content of these compounds depends on the cultivar. Before marketing fruit from astringent persimmon cultivars are routinely submitted to astringency removal treatments; however, the effect of this process on flesh carotenoids has not yet been studied in depth. This work aimed to evaluate the effect of the deastringency treatment based on high CO2 concentration on carotenoids content of persimmon fruit. To this end, total and individual carotenoids were determined in four astringent cultivars ('Aizumishirazu-A', 'Hachiya', 'Giombo' and 'Rojo Brillante') at harvest and after fruit submitted to CO2-deastringency treatment (95% CO2, 24 h, 20°C, 90% RH). Our results corroborated that the total carotenoids content depends on the cultivar, the highest content at harvest being detected in 'Hachiya' and 'Aizumishirazu-A'. The main carotenoids present in the flesh of persimmons were β-cryptoxanthin, lutein, violoxanthin, zeaxanthin, and β-carotene; in the four studied cultivars, β-cryptoxanthin was the predominant carotenoid. The CO2-deastringency treatment did not affect the total carotenoids content of 'Rojo Brillante' and 'Hachiya'. However, CO2 treatment resulted in increased carotenoids content in 'Aizumishirazu-A' and 'Giombo', and lutein and β-cryptoxanthin were the carotenoids that most markedly increased after astringency removal.